Enterococcus faecalis leakage in MTA silver amalgam and glass ionomer as root-end filling materials - Pineda Mejía, Martha Elena (2008)
One of the aims of a root-end filling material placed in an apicectomy treatment is to provide apical seal that can inhibits the coronary migration of antigens to perirradicular tissues. Many materials are used for this end; however, to date there has not been any material that satisfies all the requirements of an ideal material. With the purpose of making a comparative analysis of the apical sealing abilities of three root-end filling materials: silver amalgam, glass ionomer and MTA (mineral trioxide aggregate), in the leakage process of Enterococcus Faecalis bacteria and the time used for it to leak via coronary toward the perirradicular area, the present investigation was made. Leakage was proven when veering the fenol red glucose, in which the apexes of the sample teeth were submerged, to a temperature of 37ºC. The results showed that specimens that leakage in longer than 70 days were significantly higher for the cases of cement MTA than for the other two materials.